Salvation Colony. - Asong, Linus T. (Linus Tongwo), 1947-2012 (Langaa RPCIG, 2009)
Dennis Nunqam Ndendemajem, the spectral social misfit of No Way To Die, having failed to die by suicide, is pursued by the hatred of friends and family relations. He seeks refuge in The Salvation Colony of the Angels of Limbo Church of Africa - a veritable paradise for all whom society has sidelined and whom chance or choice have led thereto. Refuge Dennis finds at the Salvation Colony, thanks to the kindly founding spiritual and material patron, the highly reputable but extremely devilish Pastor Sixtus Shrapnell, fondly referred to as Our Father. At the Colony, though completely dehumanized.